The bonds of family : slavery, commerce and culture in the British Atlantic world - Donington, Katie; Lester, Alan; Thompson, Andrew (Manchester : Manchester University Press, 2019)
Moving between Britain and Jamaica this book reconstructs the world of commerce, consumption and cultivation sustained through an extended engagement with the business of slavery. Transatlantic slavery was both shaping of and shaped by the dynamic networks of family that established Britain's Caribbean empire. Tracing the activities of a single extended family - the Hibberts - this book explores how slavery impacted on the social, cultural, economic and political landscape of Britain. It is a history of trade, colonisation, enrichment and the tangled web of relations that gave meaning to the transatlantic world. The Hibberts's trans-generational story imbricates the personal and the political, the private and the public, the local and the global. It is both the intimate narrative of a family and an analytical frame through which to explore Britain's history and legacies of slavery.
Moving between Britain and Jamaica this book reconstructs the world of commerce, consumption and cultivation created and sustained through an extended engagement with the business of slavery. Transatlantic slavery was both shaping of and shaped by the dynamic networks of family that established and expanded Britain's Caribbean empire. Tracing the activities of a single extended family - the Hibberts - this book explores how the system of slavery impacted on the social, cultural, economic and political landscape of Britain during the period leading up to, during and after abolition. It is a history of trade, colonisation, enrichment and the tangled web of relations that gave meaning to the transatlantic world. The Hibberts's trans-generational story imbricates the personal and the political, the private and the public, the local and the global. It is both the intimate narrative of a family and an analytical frame through which to explore Britain's multifaceted engagement with the business of slavery. The book contributes to a growing scholarship on imperial families and in particular those who operated within the world of the transatlantic planter-merchant elite. It integrates an analysis of the family as political and economic actors with an examination of their activities within the domestic and cultural sphere to provide an overview of the different ways in which slavery shaped society both in the colony and the metropole. This book will appeal to scholars and students interested in slavery studies, British imperialism, local and family history, cultural history, museum studies, gender history, and histories of business and commerce in the eighteenth and nineteenth century -- Back cover.
Introduction: Family matters -- slavery, commerce, and culture Part I: Family business -- commerce, commodities, and credit 1. Manchester 2. Jamaica
Description based on CIP data; resource not viewed.
JSTOR
Keywords: Hibbert family; Hibbert family; Slavery -- Great Britain -- Colonies -- History; Slavery -- Jamaica -- History; Slavery -- Colonies; Slavery; Slavery -- British colonies; Great Britain; Jamaica; HISTORY / United States / Colonial Period (1600-1775); History